2009
DOI: 10.1177/0731684408100268
|View full text |Cite
|
Sign up to set email alerts
|

Analytical Investigation and Comparative Assessment of Interphase Influence on Elastic Behavior of Fiber Reinforced Composites

Abstract: Interfacial interactions and interphases play a key role in all fiber reinforced composites. However, a clear distinction must be made between interface and interphase. Interphase becomes interface if its thickness decreases to zero. In most of the available micromechanical models the interface is considered perfect (no interphase). However, such a condition is hardly fulfilled in real composites. It is possible to find the volume of interphase by using DSC or identification of interphase region using SEM or s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 26 publications
2
18
0
Order By: Relevance
“…They recognised, however, that at small interphase thicknesses (of the order of 210 nm) nanoindentation measurements may be affected by the proximity of the fibre. It appears then, that transition regions may not be representative of the material properties and it has been suggested by other researches, that observations of such a transition at a fibre-matrix interface may be the consequence of a locally constrained matrix region in the vicinity of the reinforcement [9,10]. This suggestion is consistent with Finite Element Analysis work, which indicates that even a perfect interface would lead to an observed interphase region of apparently varying elastic properties [6].…”
Section: Introductionsupporting
confidence: 73%
See 1 more Smart Citation
“…They recognised, however, that at small interphase thicknesses (of the order of 210 nm) nanoindentation measurements may be affected by the proximity of the fibre. It appears then, that transition regions may not be representative of the material properties and it has been suggested by other researches, that observations of such a transition at a fibre-matrix interface may be the consequence of a locally constrained matrix region in the vicinity of the reinforcement [9,10]. This suggestion is consistent with Finite Element Analysis work, which indicates that even a perfect interface would lead to an observed interphase region of apparently varying elastic properties [6].…”
Section: Introductionsupporting
confidence: 73%
“…Figure 7 also shows a region of significantly lower elastic modulus (compared with the vinylester). Overall, the transition region shown in Figure 7 is approximately four times the size of the indentation width, perhaps suggesting that the change in material property may only be partially attributed to measurement artefact [10,11]. Two possible contributions to the observed transition region are considered below.…”
Section: Insert Figurementioning
confidence: 97%
“…They concurred that the more flexible the fibres are, the more pronounced their effect on the rheological characteristics is [7] [8] [9]. A recent study on the effect of fibre-length distribution on the rheological behavior of castor-oil composite showed that at high fibre length, the shear viscosity becomes more dependent on shear rate [10]. This behavior is due to elastic deformation of the fibres [10].…”
Section: Introductionmentioning
confidence: 62%
“…A recent study on the effect of fibre-length distribution on the rheological behavior of castor-oil composite showed that at high fibre length, the shear viscosity becomes more dependent on shear rate [10]. This behavior is due to elastic deformation of the fibres [10].…”
Section: Introductionmentioning
confidence: 99%
“…The interface thicknesses of both glass fiber-matrix interface and carbon fiber-matrix interface were taken as 1.0 µm (slightly larger than the CNT length of 0.8 µm). According to [47,48], the soft interface layer can be assigned the elastic modulus of E i =(E CNT +E mtrix )/20 while the stiff interface layer can be assigned a higher Young's modulus as E i =(E CNT +E mtrix )/2. The interface stiffness can vary therefore in the range from soft to stiff, with the ratio E i /E matrix from 0.55 to 5.5.…”
Section: 4mentioning
confidence: 99%